Factors associated with institutionalization among home-dwelling patients of Urgent Geriatric Outpatient Clinic: a 3-year follow-up study - Salminen Marika; Laine Jonna; Vahlberg Tero; Viikari Paula; Wuorela Maarit; Viitanen Matti; Viikari Laura (SPRINGER, 2022)
Purpose To examine the effect of predictive factors on institutionalization among older patients.
Methods The participants were older (aged 75 years or older) home-dwelling citizens evaluated at Urgent Geriatric Outpatient Clinic (UrGeriC) for the first time between the 1st of September 2013 and the 1st of September 2014 (n = 1300). They were followed up for institutionalization for 3 years. Death was used as a competing risk in Cox regression analyses.
Results The mean age of the participants was 85.1 years (standard deviation [SD] 5.5, range 75-103 years), and 74% were female. The rates of institutionalization and mortality were 29.9% and 46.1%, respectively. The mean age for institutionalization was 86.1 (SD 5.6) years. According to multivariate Cox regression analyses, the use of home care (hazard ratio 2.43, 95% confidence interval 1.80-3.27, p < 0.001), dementia (2.38, 1.90-2.99, p < 0.001), higher age (>= 95 vs. 75-84; 1.65, 1.03-2.62, p = 0.036), and falls during the previous 12 months (>= 2 vs. no falls; 1.54, 1.10-2.16, p = 0.012) significantly predicted institutionalization during the 3-year follow-up.
Conclusion Cognitive and/or functional impairment mainly predicted institutionalization among older patients of UrGeriC having health problems and acute difficulties in managing at home.Key summary pointsAim To examine the effect of predictive factors on institutionalization among home-dwelling patients of Urgent Geriatric Outpatient Clinic during a 3-year follow-up. Findings The rates of institutionalization and mortality were 29.9% and 46.1%, respectively. The use of home care, dementia, higher age and falls during the previous 12 months significantly predicted institutionalization during the follow-up. Message Cognitive and/or functional impairment mainly predicted institutionalization among older patients of UrGeriC having health problems and acute difficulties in managing at home.